The design, construction, characterization and application of 9μm optical parametric chirped-pulse amplifier - Qu, Shizhen (Nanyang Technological University, 2020)
The high energy, high average power, ultrafast long-wavelength-infrared (LWIR, 8-15μm) laser sources have become an emerging research domain in recent years due to their extensive applications, for instance the advanced molecular spectroscopy, and the strong field experiment (soft and hard X-ray generation and light induced electron acceleration, and the isolated attosecond pulse generation, etc.). Among all the high energy, ultrafast laser techniques, the optical parametric chirped pulse amplification (OPCPA) attracts a lot of interests thanks to its high energy scalability, broad gain bandwidth, low thermal load and wide wavelength tunability. Nowadays, the operating wavelength range of the high energy ultrafast OPCPA system has been pushed towards the >8 μm longer wavelength mid-IR regime. However, the challenges of developing the ultrafast, longer wavelength mid-IR OPCPA lies in the scaling-up of its output energy, average power and bandwidth. In this dissertation, the gain bandwidth limitation of a longer wavelength mid-IR OPCPA is demonstrated. This limitation is introduced by the significant dispersion in the NIR regime which approaches to the band gap of the nonlinear medium. The substantially increased dispersion causes the stronger group velocity mismatch between the NIR pump/signal and the LWIR idler which inhibits a large gain bandwidth. In order to overcome the limitation, one way is to introduce a non-collinear phase matching geometry in the parametric amplification. A general analytical model of the gain bandwidth which could be applied to the non-collinear OPA/OPCPA is demonstrated. Compared with the traditional gain bandwidth model, the proposed model breaks through the constrain about the direction of the idler wave vector and could enhance 5% accuracy of the gain bandwidth evaluation, especially in the longer wavelength mid-IR regime. By applying the proposed model to the OPCPA, the relations between the gain bandwidth and the key design parameters such as the non-collinear angle, pump intensity and crystal length are revealed. Based on the theoretical analysis, an angular-dispersive OPA method is proposed to enhance the gain bandwidth of the parametric amplification. Using a large band gap material as the nonlinear medium is another way to enhance the gain bandwidth of OPCPA. Based on the large band gap LiGaS2 crystal, we designed and implemented, to the best of our knowledge, the first LWIR OPCPA at 9μm wavelength driven by the 1μm Yb:YAG pump laser. The OPCPA could provide 9μm pulses with 145fs pulse duration and 14μJ pulse energy and 140mW average power. Sophisticated dispersion management is conducted with considering both higher order dispersion and the optical parametric phase which cannot be ignored in the LWIR regime. In order to further compress the LWIR pulse to single-cycle regime, we study the supercontinuum (SC) generation and self-compression in the anomalous dispersive materials including the KrS-5, ZnSe and GaAs. It is the first, to the best of our knowledge, experimental investigation on the LWIR pulse self-compression in solids with the occurrence of filamentation. The LWIR could be utmost compressed to 45fs, 1.5 optical cycle in the 5mm KrS-5. An over 5-octave spanning SC spectrum is measured in the 9mm ZnSe crystal. The experiment results also indicate the crucial roles of the filamentation and dispersion in assisting the spectrum broadening and pulse self-compression. At last, the LWIR OPCPA system is applied to produce the high harmonic generation (HHG) in solid ZnSe material. The generated high harmonic spectrum includes the up-to 24th order harmonic peaks. The cutoff energy is measured as 3.31eV which is 0.61eV higher than previously reported HHG in ZnSe driven by the MWIR laser. The measurement result is proved to be reliable and repeatable. The experiment result shows that the HHG process is a non-perturbative light matter interaction. It also shows that the linear dependence of the cutoff energy with respect to the driving wavelength is still fulfilled in the LWIR region.